Hydroclimatic Controls on the Isotopic (δ18 O, δ2 H, d-excess) Traits of Pan-Arctic Summer Rainfall Events - Mellat Moein; Bailey Hannah; Mustonen Kaisa-Riikka; Marttila Hannu; Klein Eric S.; Gribanov Konstantin; Bret-Harte M. Syndonia; Chupakov Artem V.; Divine Dmitry V.; Else Brent; Filippov Ilya; Hyöky Valtteri; et al. (FRONTIERS MEDIA SA, 2022)
Arctic sea-ice loss is emblematic of an amplified Arctic water cycle and has critical feedback implications for global climate. Stable isotopes (delta O-18, delta H-2, d-excess) are valuable tracers for constraining water cycle and climate processes through space and time. Yet, the paucity of well-resolved Arctic isotope data preclude an empirically derived understanding of the hydrologic changes occurring today, in the deep (geologic) past, and in the future. To address this knowledge gap, the Pan-Arctic Precipitation Isotope Network (PAPIN) was established in 2018 to coordinate precipitation sampling at 19 stations across key tundra, subarctic, maritime, and continental climate zones. Here, we present a first assessment of rainfall samples collected in summer 2018 (n = 281) and combine new isotope and meteorological data with sea ice observations, reanalysis data, and model simulations. Data collectively establish a summer Arctic Meteoric Water Line where delta H-2 = 7.6.delta O-18-1.8 (r(2) = 0.96, p < 0.01). Mean amount-weighted delta O-18, delta H-2, and d-excess values were -12.3, -93.5, and 4.9 parts per thousand, respectively, with the lowest summer mean delta O-18 value observed in northwest Greenland (-19.9 parts per thousand) and the highest in Iceland (-7.3 parts per thousand). Southern Alaska recorded the lowest mean d-excess (-8.2%) and northern Russia the highest (9.9 parts per thousand). We identify a range of delta O-18-temperature coefficients from 0.31 parts per thousand/degrees C (Alaska) to 0.93 parts per thousand/degrees C (Russia). The steepest regression slopes (>0.75 parts per thousand/degrees C) were observed at continental sites, while statistically significant temperature relations were generally absent at coastal stations. Model outputs indicate that 68% of the summer precipitating air masses were transported into the Arctic from mid-latitudes and were characterized by relatively high delta O-18 values. Yet 32% of precipitation events, characterized by lower delta O-18 and high d-excess values, derived from northerly air masses transported from the Arctic Ocean and/or its marginal seas, highlighting key emergent oceanic moisture sources as sea ice cover declines. Resolving these processes across broader spatial-temporal scales is an ongoing research priority, and will be key to quantifying the past, present, and future feedbacks of an amplified Arctic water cycle on the global climate system.